Medición y evaluación en comunicación estratégica. Caso de estudio Ministerio de Cultura y Patrimonio del Ecuador - Peñaherrera Jaramillo, Ivonne Alexandra (2014)
Nowadays, the strategic planning in communication is an important contribution in determining the objectives inside the organization. This present research work was aimed to analyzed the process of strategic communication planning from a model for measuring and evaluating the case of study VI Feria Internacional del Libro Quito 2013 developed by Ministry of Culture and Heritage of Ecuador. The final results showed that although is substantial evaluate continually the organizational communication, is a concept that is not set in the organization yet. Finally, it can be concluded that strategic communication is an important part of the organization and thanks to this; it has provided them easily the planning and implementation of organizational strategic priorities and joint participation of all people who work there